Scripting Online Social Interaction - Cheng, Lili; Chesley, Harry; Farnham, Shelly; Landau, Jennifer; Seban, Suzana (2001)
Scripting of social interaction is commonplace in off-line systems. On-line, this technique can be even more effective, using the computer as mediator. To investigate this area, we implemented a prototype system named Lead Line that adds scripting to plain text chat. Using Lead Line, we ran a number of informal trials and conducted an experiment in structured versus unstructured interaction in a goal-directed task. We learned a number of things, some confirming previous results, and some new: brainstorming and assessment tasks work well when scripted; lessons users learn from a script persist; structure enables creativity; familiar contexts can enable communication; identity is a tool; and roles can empower the user.